2016
DOI: 10.1073/pnas.1516947113
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive fatigue influences students’ performance on standardized tests

Abstract: Using test data for all children attending Danish public schools between school years 2009/10 and 2012/13, we examine how the time of the test affects performance. Test time is determined by the weekly class schedule and computer availability at the school. We find that, for every hour later in the day, test performance decreases by 0.9% of an SD (95% CI, 0.7-1.0%). However, a 20-to 30-minute break improves average test performance by 1.7% of an SD (95% CI, 1.2-2.2%). These findings have two important policy i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
99
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 141 publications
(111 citation statements)
references
References 21 publications
5
99
1
1
Order By: Relevance
“…This finding is also borne out in laboratory tests using controlled computerized paradigms (Helton and Russell, 2015;Lim and Kwok, 2016) where rest breaks interrupt the trajectory of TOT declines. In educational settings, Sievertsen et al (2016) studied a large cohort of Danish students and found that test performance improved significantly following 20-30-min breaks during the school day. The balance of evidence is thus that rest pauses have positive effects on cognitive functioning, at least in the short term.…”
Section: Countermeasures: Napping and Rest Breaksmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding is also borne out in laboratory tests using controlled computerized paradigms (Helton and Russell, 2015;Lim and Kwok, 2016) where rest breaks interrupt the trajectory of TOT declines. In educational settings, Sievertsen et al (2016) studied a large cohort of Danish students and found that test performance improved significantly following 20-30-min breaks during the school day. The balance of evidence is thus that rest pauses have positive effects on cognitive functioning, at least in the short term.…”
Section: Countermeasures: Napping and Rest Breaksmentioning
confidence: 99%
“…In educational settings, Sievertsen et al . () studied a large cohort of Danish students and found that test performance improved significantly following 20–30‐min breaks during the school day. The balance of evidence is thus that rest pauses have positive effects on cognitive functioning, at least in the short term.…”
Section: Introductionmentioning
confidence: 99%
“…Many psychological and occupational medicine studies indicate the crucial significance of fatigue: the short-term impact on the ongoing performance of duties in the form of, for example, attention alteration or efficiency reduction (e.g., in the work of a driver, flight controller or a hospital staff member) [1]; the long-term impact related to "burnout" [2] and absences from work [3]. Increasing data indicate a growing problem with fatigue among students [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…However, few such studies exist, and evidence is contradictory, with some studies providing evidence for real-world ego-depletion effects (e.g. Dai, Milkman, Hofmann, & Staats, 2015;Sievertsen, Gino, & Piovesan, 2016) and others not (e.g. O'Connell et al, 2008;Randles, Harlow, & Inzlicht, 2017).…”
Section: Evidence For Ego Depletion In Daily Lifementioning
confidence: 99%